"FINANCIALIZATION" OF CAPITALISM AND ITS RECENT EFFECTS ON LATIN AMERICAN EMERGENT ECONOMIES. (1st October 2010) - Unknown
Abstract : This article intends to raise a discussion concerning the role and importance of financial dominance as a component that characterizes the existing regime of capital accumulation of the world economy. This approach has scarcely been included in the analysis of today's economic crisis that is impacting the world economy. The article also intends to show how the speculative financing of big enterprises has contributed to the crisis of the regime of financial dominance accumulation. A basic premise raised in this analysis is that large conglomerates try, at all costs, to offer expressive returns to their shareholders in exchange for financial resources granted by economic agents in the stock exchange markets—in other words, returns generated by "fictitious capital." Many emergent economies became loci for patrimonial and financial valorization. In Latin America, for example, the financial dominance accumulation regime is based mainly on the continuous growth of the public securities debt, backed by extremely high interest rates on government securities. It has resulted in an increase in the inflows of short-term capitals, which favored the appreciation of their national currencies. As a consequence, the Latin American emergent economies are experiencing a return to balance of payments deficits. In short, an increase in dependency and economic and political domination by the internationalized capital.